La città tra romanzo e studi urbani/ The city between novels and urban studies - Scandurra, Giuseppe (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2017)
The focus of this study is the relationship between literature and urban studies. This relationship comes into view when novels and anthropologists tackle the modern and contemporary city. Today we are aware of how our “non-fiction”, our scientific writing, is just one of the many writing machines, not always clearly distinguishable among each other. What kind of writing is “Gomorrah”, we started asking several years ago? An essay, a novel, a piece of journalism, of literature, an ethnography? What’s the role of fiction in it? To answer this question we have to go back to a time when disciplines were less institutionalized and see how the literary set of images was conceived and influenced by urban scholars, and vice versa, in order to determine the moment when the “two cultures”, ie literature and scientific production, have influenced each other. In addition, the city was born with modernity. Novel was born with modernity. The first urban ethnographies were born with the birth of the city and of what we call “modern”. How much, how and why do these three words work together?